How does influencer marketing impact brands in the sportswear industry? : exploring the effects of brand coolness, brand attitude and purchase intentions - Jäkel, Lena Johanna (2020)
This study aims to investigate the impact of using influencers on Instagram as a communication tool for sportswear brands. While exploring this research field, brand attitude and the newly developed construct of brand coolness were evaluated for their effects on purchase intentions. Moreover, the current study evaluates whether the number of influencers´ followers influences the results. For that matter, an experimental study was conducted with comparison between subjects among three groups. Those three groups were designed to test brand attitude, brand coolness and purchase intentions of participants being exposed to influencer’s posts or brand’s posts. Further, the influencer marketing conditions differed in the number of followers (high number of followers/ low number of followers) to investigate the effects. Quantitative data of 310 participants was collected through an online survey and analysed. The results of this study found no significant difference for influencer’s posts compared to brand’s posts on the constructs brand attitude, brand coolness and purchase intentions, besides one exception: The dimension ‘Rebellious’ of brand coolness. Furthermore, the impact of using influencers with a high number of followers for the brand coolness dimensions ‘Desirability’ and ‘Positive Autonomy’ was proven to be positive. The study is the first one connecting brand coolness with the construct of purchase intentions and confirms a positive significant impact of all dimensions on purchase intentions. The results show that the brand coolness dimensions have a positive significant impact on brand attitude. Finally, this study provides an outlook on future research and limitations are discussed.